Wychowanie w rodzinie i dla rodziny osób dorosłych w świetle instytucji oświatowych - Kierzkowska, Iryna (Karkonoska Państwowa Szkoła Wyższa, 2012)
The issue of family education is one of the most recent social problems. Reflections on the problems of education in the family life of adults was the basis of the study aimed at investigating the state of readiness of adults to live together in the family in the contemporary society, the propositions of the educational institutions regarding the attempts to solve some of the problems of the education in family life, and the direct recipients of the educational influence – in other words, the adults.
Keywords: rodzina; wychowanie; dorośli; edukacja; instytucje oświatowe